2000
DOI: 10.1109/77.828465
|View full text |Cite
|
Sign up to set email alerts
|

Cu-Nb and Cu/stainless steel winding materials for high field pulsed magnets

Abstract: 1 h promising types of CuiStrinless Steel (SS) inrcrocoiiipositc and Cu-Nb microcomposite winding wircs for lnrge scnled tiigli ficld pulscd mngiicts nrc reviewed.l'hc cstiination o f tlic potentially nchicvnble combinations of mechanical and electrophysicat properties has bceri done. Thc fcatrires o f corresponding manufncturing proccsses foi' CulSS and Cu-Nb wircs arc prescnted. The strength -conductivity propcrtics o f severi4 types of Cu-Nb and CulSS conductors nre given. nolationships Iicfrvcon the micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Up to now, reinforced copper-based wires have shown the best compromise between these two criteria; in particular, the copper/niobium (Cu/Nb) system has been studied for decades since it has very good mechanical properties that are much better than rule-of-mixture (ROM) predictions when the size of the Nb filaments is reduced to the sub-micrometer range. It should be emphasized that two main fabrication routes have been studied: production of nanofilamentary Cu/Nb wires via severe plastic deformation (SPD) of: (i) arc-melted Cu-Nb ingots, initially consisting of a Cu matrix containing Nb dendrites, so-called ''in situ'' composites; and (ii) bulk Cu tubes and Nb rods, giving rise to a Cu matrix containing Nb continuous filaments, so-called ''continuous'' composites [2][3][4][5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, reinforced copper-based wires have shown the best compromise between these two criteria; in particular, the copper/niobium (Cu/Nb) system has been studied for decades since it has very good mechanical properties that are much better than rule-of-mixture (ROM) predictions when the size of the Nb filaments is reduced to the sub-micrometer range. It should be emphasized that two main fabrication routes have been studied: production of nanofilamentary Cu/Nb wires via severe plastic deformation (SPD) of: (i) arc-melted Cu-Nb ingots, initially consisting of a Cu matrix containing Nb dendrites, so-called ''in situ'' composites; and (ii) bulk Cu tubes and Nb rods, giving rise to a Cu matrix containing Nb continuous filaments, so-called ''continuous'' composites [2][3][4][5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The stressed condition of the crystallographic lattices of the components in Cu-Nb microcomposite material has been confirmed by X-ray analysis [13]. In particular it has been shown that crystallographic lattice of copper is compressed in longitudinal direction parallel to the axis of deformation by drawing and consequently is stretched in the transverse direction.…”
Section: Introductionmentioning
confidence: 88%
“…These alloys were prepared by vacuum arc melting using a consumable electrode and subsequently enclosed in a copper case and subjected to cold drawing deformation with intermediate annealings at 350-500°C. The preparation procedure of the nanocomposite conductors by melting followed by cold deformation and results of the study of their electromechanical properties are described in [4,19,20]. The total degree of cold deformation by drawing for samples subjected to fatigue tests was ln (A 0 /A) = 7-9, where A 0 and Across sectional area of the sample before drawing and after drawing, respectively.…”
Section: Methodsmentioning
confidence: 99%